Study on Unitless Physics III: Focused Particle Communication, Evolution of Fundamental Physics and the Universe US9-3 - James W. Christy (Research Trends and Challenges in Physical Science Vol. 4, 2021)
Particle communication arising from rest energy enables conversion of random motion to organized motion. A major failing of the Standard Model of Physics is an inability to produce angular momentum conservation from random motion, an inability to explain nonlocality in QM and lack of explanation for the similar morphology of spiral galaxies and hurricanes, and for the causes of helicity conservation in water, and for tornados and jet streams in the atmosphere and galaxies. The solutions require selective particle to particle communication and subsequent particle action to a state of higher organization. Particle to particle focused communication is required in many circumstances to evolve random velocities into ordered velocity states. This paper, based on US9-1 and US9-2, explores the possibility of new particle to particle forces via rest energy which enable higher organization. An ability in Physics to deal with the above would provide physics which could be useful to biological science which presently describes numerous varieties of particle to particle communications in very complex organizations. Control of tornados via interference of particle to particle communication can be possible with future technology. The effects of focused particle to particle communication can replace the concepts of dark matter and nuclear force bosons. Focused selective particle to particle communication enables evolution in Physics and the Universe which leads to quantum mechanics and biological evolution. The mathematics of QM is fundamental in this process, but this paper asserts that there are simpler predecessors of QM within particle communication and internal processing of fundamental particles. Selective particle communication enables evolution of Physics to states of higher organization. This possibility is not recognized in Standard Physics. The possibilities regarding the Universe and Cosmology are extensive. The introduction of focused particle to particle communication from rest energy in addition to gravity and E&M enables creative interactions which can solve many of the mysteries inherent in current understanding: Dark matter, dark energy, lattice structure of the Universe and inter-galactic voids.